Revalorizing mircea eliade’s notion of revalorization: reflections on the present-day re-uses of mesoamerica’s pre-columbian sites and architecture - Jones, Lindsay (Archaeus, 2011)
Though Mircea Eliade’s use of the term of "revalorization" is only intermittent in his written work, it is arguably a central theme in his understanding of the ways in which religious traditions invariably "make meaning" by retrieving and refashioning ideas and practices from previous traditions. His History of Religious Ideas, for instance, directs attention to the creative and interested, if often poorly informed, means by which religious communities undertake this sort of resuscitation of earlier traditions, which they inevitably warp and wedge to their current purposes. I extend - or "revalorize" - the term, moreover, to address the creative if sometimes poorly informed ways in which scholars have appropriated concepts from Eliade, and then put those formulations to service (or maybe disservice) in their own interpretive projects. In that spirit, I reutilize Eliade’s notion of revalorization, together with his ample comments on religious symbols, as a means of respecting the ever-shifting, still-emergent usages and meanings of centuries-old Mesoamerican ruins. On the basis of that exercise, I conclude that Eliade’s variously revered and maligned corpus, when engaged in suitably inventive and strategic ways, remains relevant, challenging and useful in the extreme.